Caracterização litoestrutural do embasamento do Orógeno Araçuaí entre os municípios de Iúna (ES) e Governador Valadares (MG) - Paulo Zaeyen de Oliveira e Silva (2016)
The area of study chosen is part of the geotectonic Araçuaí-Western Congo Orogen context. The basement units of the Araçuaí Orogen evolved from the assemblage of the Archean crustal blocks during the Paleoproterozoic orogenic process that lasted between 2.2 and 2.0 Ga. The Mantiqueira, Juiz de Fora and Pocrane orthogneisses complexes correspond to the Paleoproterozoic basement rocks of the southern Araçuaí Orogen. The purpose of this research is to present a series of E-W lithostructural cross sections between the municipalities of Iúna (ES), Manhumirim and Governador Valadares (MG), locating the study area in the high grade metamorphic and igneous core of the southern Araçuaí Orogen. Therefore, a geometric descriptive analysis of each lithology and of the contact relationships between the Pocrane and Juiz de Fora complexes, and Pocrane and Mantiqueira complexes was made. This research also presents, as an important unit of the Araçuaí basement, recent data about the Caparaó Suite and the adjacent regions to the Caparaó mountain range.